Associations of phthalates with NAFLD and liver fibrosis: A nationally representative cross-sectional study from NHANES 2017 to 2018 - Chen, Xingying; Tian, Feng; Wu, Jianfeng; Liu, Lan; Li, Ye; Yu, Genfeng; Duan, Hualin; Jiang, Yuqi; Liu, Siyang; He, Yajun; Luo, Yaosheng; Song, Cheng; et al. (Frontiers in Nutrition, 2022)
Although phthalates are common environmental pollutants, few studies have focused on the relationship of phthalate exposure with non-alcoholic fatty liver disease (NAFLD) or liver fibrosis, and especially, the alternative phthalates have been questioned in recent years about whether they are better choices. Thus, this study aimed to explore the associations of exposure to major phthalates or alternative phthalates with NAFLD and liver fibrosis in 1450 adults from the National Health and Nutrition Examination Survey (NHANES) 2017-2018. The urinary metabolite concentrations of phthalates were detected. Controlled attenuation parameter (CAP) and median liver stiffness measurement (LSM) were acquired for quantitative diagnosis of NAFLD and liver fibrosis by vibration-controlled transient elastography to detect the associations of di-2-ethylhexyl phthalate (DEHP), diisononyl phthalate (DINP) and diisodecyl phthalate (DIDP) with NAFLD and liver fibrosis. After adjustment of the potential factors, the prevalence of NAFLD was significantly elevated among those in the fourth quartile of mono-(2-ethyl-5-carboxypentyl) phthalate (OR, 95%CI = 2.719, 1.296, 5.700, P= 0.016), mono(2-ethyl-5-hydroxyhexyl) phthalate (OR, 95%CI = 2.073, 1.111, 3.867, P= 0.037). No significant association was found between the alternative phthalates and NAFLD. The similar result was gained by linear regression analysis that MECPP was still significantly associated with Ln CAP (Q4 vs. Q1: β, 95%CI = 0.067, 0.017, 0.118, P= 0.027). After adjustment for the same covariates, no significance association between phthalates and liver fibrosis was found in logistics regression analysis. All in all, higher prevalence of NAFLD is correlated with DEHP but not DINP or DIDP in American adults. There is no significant relationship between phthalates and liver fibrosis defined as LSM≥8Kpa. Nevertheless, further research is needed to provide evidence of causality.